2004
DOI: 10.4049/jimmunol.173.4.2792
|View full text |Cite
|
Sign up to set email alerts
|

MHC Class II Isotype- and Allele-Specific Attenuation of Experimental Autoimmune Encephalomyelitis

Abstract: Most autoimmune diseases are associated with certain MHC class II haplotypes. Autoantigen-based specific immune therapy can lead either to beneficial or, in the context of inflammatory conditions, detrimental outcomes. Therefore, we designed a platform of peptides by combinatorial chemistry selected in a nonbiased Ag-independent approach for strong binding to the rat MHC class II isotype RT1.Dn allelic product of the RT1n haplotype that is presenting autoantigen in myelin oligodendrocyte glycoprotein-induced e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Therefore, the model described here can be considered to be highly relevant for the preclinical testing of novel strategies for the treatment of MS. Furthermore, it might contribute to a better understanding of the pathogenesis of MS. 29,[32][33][34] In agreement with earlier studies we demonstrate that BMT leads to disease attenuation and protects from further induced relapses with the disease-inducing antigen, strongly suggesting that this therapy is a promising option for the treatment of MS in humans. [17][18][19][20][21][22][23][24] For the first time we demonstrate in direct comparisons that protection can be achieved by MHC-matched allogeneic, syngeneic, and BM grafts from EAE-diseased DA rats.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the model described here can be considered to be highly relevant for the preclinical testing of novel strategies for the treatment of MS. Furthermore, it might contribute to a better understanding of the pathogenesis of MS. 29,[32][33][34] In agreement with earlier studies we demonstrate that BMT leads to disease attenuation and protects from further induced relapses with the disease-inducing antigen, strongly suggesting that this therapy is a promising option for the treatment of MS in humans. [17][18][19][20][21][22][23][24] For the first time we demonstrate in direct comparisons that protection can be achieved by MHC-matched allogeneic, syngeneic, and BM grafts from EAE-diseased DA rats.…”
Section: Discussionsupporting
confidence: 90%
“…Susceptibility to EAE and MS is associated with the major histocompatibility complex class II (MHC II) genes (1,2), suggesting that presentation of antigens on MHC II plays an important role in CD4 ϩ T cell activation and disease initiation. After priming of encephalitogenic T cells in the periphery, they migrate into the CNS, where they trigger inflammatory responses including microglial activation.…”
mentioning
confidence: 99%
“…3). We previously showed that the T cell restriction of MOG 91–108‐specific T cells in LEW.1N (RT1 n ) was RT1.D restricted (data not shown) 9.…”
Section: Resultsmentioning
confidence: 87%
“…Anti‐RT1.B (OX‐6) nearly completely blocked the peptide specific T cell response but not anti‐RT1.D (OX‐17) or control antibody (Tib191) (each n =4). In LEW.1N rats the MOG 91–108‐specific T cell response was RT1.D restricted (data not shown, 9). Error bars represent SEM.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation